2017
DOI: 10.1002/star.201600369
|View full text |Cite
|
Sign up to set email alerts
|

Effects of solid‐state fermentation (Aspergillus oryzae var. oryzae) on the physicochemical properties of corn starch

Abstract: The physicochemical transformations suffered by corn starch granules under the solid-state fermentative action of Aspergillus oryzae var. oryzae were studied. Light microscopy images showed that the starch granules became increasingly fractured and broke-down as fermentation time was longer. SEM micrographs showed that the mean particle diameter decreased linearly with the fermentation time, indicating a zeroth-order hydrolysis kinetics. The crystallinity content of fermented corn starch achieved a maximum val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
3
4
0
Order By: Relevance
“…These results are in good agreement with findings of Reyes et al. [ 27 ] Also, Falade et al. found a greater enthalpy value for maize flour after fermentation with L. plantarum , indicating that higher energy is needed to disrupt starch granules of fermented corn flour.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These results are in good agreement with findings of Reyes et al. [ 27 ] Also, Falade et al. found a greater enthalpy value for maize flour after fermentation with L. plantarum , indicating that higher energy is needed to disrupt starch granules of fermented corn flour.…”
Section: Resultssupporting
confidence: 92%
“…[25] During fermentation, the amorphous zone was partially destroyed, and the proportion of crystalline zone increased, resulting in an increase in To, Tp, Tc, and ΔH, which is consistent with the conclusion of pasting properties mentioned above. These results are in good agreement with findings of Reyes et al [27] Also, Falade et al found a greater enthalpy value for maize flour after fermentation with L. plantarum, indicating that higher energy is needed to disrupt starch granules of fermented corn flour. [28]…”
Section: Thermal Propertiessupporting
confidence: 92%
“…47 The ratio of the intensity of bands at 1047 and 1022 cm −1 (1047/1022) represented the ratio of ordered crystalline regions to amorphous regions in the starch. 48,49 The ratio of 1047/1022 among the three starch nanohydrogels was the highest in pea starch nanohydrogels and the lowest in potato starch nanohydrogels (Figure 6), which is consistent with the relative crystallinity results (Figure 4). The changes in the infrared (IR) ratio of 1047/1022 cm −1 following the retrogradation process suggest that the molecules of pea starch nanohydrogels with high-amylose starch more readily reassociate and reorganize into a more organized structure than the other two starches.…”
Section: Particle Size Distribution Of Starch Nanohydrogelssupporting
confidence: 83%
“…The secretion of hydrolytic enzymes in the process of metabolic fungi results in the cutting of the glycosidic bonds of starch compounds on the cell wall, causing the breakdown of complex compounds into simpler ones, namely glucose, and a decrease in starch content [29][30]. It is known from the research of Reyes et al [31] that the fermentation time of 3 days is sufficient to degrade starch granules in the material. The previous study used pure starch whereas this study used turmeric rhizome as the substrate, which is a complex medium.…”
Section: Effects Of Fermentation Time On Starch Content Of Biodegrade...mentioning
confidence: 99%